O Metamorfozach Owidiusza z Haarlemu - Rybowska, Joanna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The article considers a series of relief prints by Hendrik Goltzius. The artist intended for these prints to become an ‘illustrated companion’ to Ovid’s Metamorphoses, or, alternatively, a sort of mirror image that reflects the poetic world of Metamorphoses in another creative medium. The first part of this analysis surveys Goltzius’ creative career and examines which life events might have encouraged the artist to start working on his adaptation of Metamorphoses. In the second part of the article, we discuss the creation of Goltzius’ drawings and copperplate engravings, explaining why the work of this Haarlem artist represents a historic breakthrough in the illustrative tradition of Ovid’s Metamorphoses. Finally, the third part of the article assesses whether Goltzius’ Metamorphoses prints adhere to established conventions of the emblematic art (ars emblematica).